Urodynamics : A Quick Pocket Guide - Vignoli, Giancarlo (Springer International Publishing : Imprint: Springer, 2017)
This pocket guide is an easy-to-use, practically oriented resource that provides reliable information and advice on the technical aspects of urodynamic techniques, the interpretation of tracings, quality control, and the most common pitfalls. Individual sections focus on uroflowmetry, multichannel urodynamics, interpretation of pressure/flow tracings, urethral function studies, pelvic floor electromyography, videourodynamics, and urodynamics of the upper urinary tract. Despite recent criticisms, there is general agreement that urodynamic investigation represents a necessary step before any surgical approach to incontinence and obstruction. Nevertheless, recently published guidelines fail to provide specific directions on performance and interpretation of urodynamics, and knowledge of the basic rules and formal urodynamics training are too often lacking. Readers will find that this guide enables them to retrieve key information quickly and to feel more confident in their practice of urodynamics. .
Keywords: Medicine.; Urology.; elektronické knihy; electronic books